PERSPEKTIF HUKUM TINDAK PIDANA HAK MERK INDUSTRI BATIK DI PEKALONGAN - Nuha, Ulin; Faozi, Safik (Jurnal Ilmiah Dinamika Hukum, 2024)
Batik is a work of art that has unique cultural values. The existence of batik can be found at any time in all corners of the city of Pekalongan. Meanwhile, batik production and trading activities are active throughout the day, even late at night. The pulse of people's lives, which is never separated from batik, has given Pekalongan the image of a "batik city". This is quite relevant considering that the people of Pekalongan city cannot be separated from batik, batik has become the economic lifeblood of the people of Pekalongan. Pekalongan batik production is not only sold in the local market but has reached and penetrated the international market. As competition in the international batik industry has arrived, it is fitting for Pekalongan batik to receive legal protection. The legal protection in question is about intellectual property rights, one of which is related to the use of trademark rights. There are two problems in this research, namely how to obtain legal protection for brand rights, logos, batik motifs and models in Pekalongan and how to report criminal acts of misuse or counterfeiting batik logos/brands that have been registered with Intellectual Property Rights. This research was conducted using a normative juridical research model or a normative legal research method. The normative juridical research method is a library-based legal research method. In this research, research will be carried out by analyzing the problems being discussed relating to the regulations on Intellectual Property Rights, specifically Brand Rights. Then the author connects it with legal protection of brand rights for the Batik industry in Pekalongan. Research results Legal protection for copyright of batik motifs generally exists in the 2002 UUHC, as regulated in Article 12 letter i. Based on developments in the 1987 UUHC and 1997 UUHC, batik art that receives copyright protection is non-traditional batik art with the consideration that traditional batik art has become common property (public domain). In the 2002 Copyright Law, both traditional and contemporary batik receive protection. Legal protection for batik motif copyright is obtained automatically without registration. Copyright registration for Pekalongan batik motifs is still rarely done. UUHC 2002 basically protects the artistic work of batik craftsmen without having to register. This creates several problems, namely, new motifs created by batik craftsmen in Pekalongan are marketed, and within three months the printed batik will come out. Regarding this problem, the Pekalongan City and Regency Department of Industry and Trade has not yet taken action because basically most batik motifs in Pekalongan have not been copyrighted. If people want to protest and demand it, it will also cost a lot of money, even though most craftsmen in Pekalongan have little capital. The level of awareness and understanding of the public, especially small and medium industrial entrepreneurs, regarding copyright is still low, so this condition becomes even worse due to the lack of ability to access information, as well as understanding of relevant agency officials regarding the importance of copyright. Keywords: Brand Rights, Legal Protection, Pekalongan Batik